A supramolecular zigzag chain of organometallic dipoles mediated by PF6 2- anions - Duarte, M. Teresa (2005)
Complex {Fe( 5-cyclopentadienyl)(PMe3)[P(OPh)3](4–NCC6H4NO2)} [PF6] has been characterized by spectroscopic and X-ray diffraction in order to evaluate the tuning of the electron density at the metal center and the extension ofthe delocalization on the molecule due to the presence of phosphite and phosphine co-ligands. The compound crystallizes in the centrosymmetric space group P21/c which destroys the possibility of exhibiting any quadratic NLO properties. The packing shows a supramolecular zigzag chain of antiparalell dimmers connected via the PF6 anions with C—H—F −distances ranging from 2.389 (7) to 2.667 (6)°A . Each zigzag chain is composed by isomeric organometallic fragments containing either R or S molecules. These chains are connected through weak intermolecular interactions (C—H· · ·C) forming a two dimensional plane along [101].